Hikayat Raja Pasai Sebagai Sumber Historiografi Menurut Perspektif Syed M. Naquib Al-Attas - Wilandra, Syaidina Sapta (TSAQAFAH, 2023)
Hikayat Raja Pasai (The Chronicles of Pasai) is considered one of the oldest texts that tells about Islamization in the Malay-Indonesian region. According to other traditional historiography, this hikayat by Western scholars is often regarded as a story full of myths and very subjective so its credibility is judged to be reduced, even considered as a mere fantasy story. This opinion was rejected by Syed M. Naquib Al-Attas. According to him, the results of the interpretation of Western scholars were due to their biased worldview, so they built a secular historical research methodology. As a result, they consider traditional historical works such as Hikayat Raja Pasai to be only literary works. That's why Al-Attas then tried to re-interpretation the Hikayat Raja Pasai which is the oldest historiographical work that explains the process of Islamization in the Malay-Indonesian Archipelago. Among the results of his interpretation of this hikayat is that the name Samudra comes from the word semutraya, the process of Islamization mentioned in the hikayat has been going on since the 9th or 10th century AD and was brought by the Quraysh Arabs from Mengiri, Merah Silu is a fictional character, and Malik as-Saleh was not the first Muslim king from Samudra Pasai.